2023
DOI: 10.1007/s11606-023-08222-3
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Correlates of Uptake of Continuous Glucose Monitors Among Adults with Type 2 Diabetes in Primary Care and Endocrinology Settings

Abstract: Background Clinical trials indicate continuous glucose monitor (CGM) use may benefit adults with type 2 diabetes, but CGM rates and correlates in real-world care settings are unknown. Objective We sought to ascertain prevalence and correlates of CGM use and to examine rates of new CGM prescriptions across clinic types and medication regimens. Design Retrospective cohort using electronic health records in a large academic medical center in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…While CGMs are not yet part of routine care in individuals at risk for or with non-insulin-treated T2D, multiple studies point to their acceptability, growing use, and potential benefits in this population 18 23 . Notably, a recent study at a large medical center showed a 125% increase in CGM prescriptions in primary care setting between 2020 to 2021, with 28% of these new users not on insulin 24 . These data suggest more widespread adoption of CGM in the near future in our target cohort of individuals at risk for or with T2D not on insulin, which makes real-world implementation of our probabilistic dawn phenomenon approach more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…While CGMs are not yet part of routine care in individuals at risk for or with non-insulin-treated T2D, multiple studies point to their acceptability, growing use, and potential benefits in this population 18 23 . Notably, a recent study at a large medical center showed a 125% increase in CGM prescriptions in primary care setting between 2020 to 2021, with 28% of these new users not on insulin 24 . These data suggest more widespread adoption of CGM in the near future in our target cohort of individuals at risk for or with T2D not on insulin, which makes real-world implementation of our probabilistic dawn phenomenon approach more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Data from centers for medicare & medicaid services have demonstrated that Black and Hispanic/Latino adults with T2D are prescribed CGM at lower rates than White adults 88 . In a study of CGM use in T2D at a large academic medical centre, prescription of CGM was associated with younger age, private insurance, basal‐bolus insulin use, endocrinologist visits, and higher HbA1c levels 89 . Similarly, younger age and endocrinologist visits have been associated with greater likelihood of insulin pump initiation in T2D 90 .…”
Section: Improving Access To Digital Health Technologies For People W...mentioning
confidence: 99%
“… 88 In a study of CGM use in T2D at a large academic medical centre, prescription of CGM was associated with younger age, private insurance, basal-bolus insulin use, endocrinologist visits, and higher HbA1c levels. 89 Similarly, younger age and endocrinologist visits have been associated with greater likelihood of insulin pump initiation in T2D. 90 Recommendation: Both HCL systems and SIPs are currently understudied in T2D, and additional research on inequities in use and how the use of these devices may improve disparities in outcomes is necessary.…”
Section: Improving Access To Digital Health Technologies For People W...mentioning
confidence: 99%